The maximum phonation time as marker for voice treatment efficacy: a network meta-analysis - Latoszek, Ben Barsties von; Watts, Christopher R.; Schwan, Katharina; Hetjens, Svetlana (Clinical otolaryngology, 2023)
Purpose There is a diversity in treatment approaches for voice therapy in which aerodynamic treatment effects between the approaches are lacking. The evidence of voice treatments on the maximum phonation time (MPT) was quantified using the statistical approach of a network meta-analysis (NMA). Data Sources Three databases and manual search from inception to November 2021 were evaluated. Study Selection Studies were considered which were reports of randomised controlled/clinical trials (RCT) evaluating the efficacy of a specific voice therapy treatment using MPT as an outcome measure in adult participants with voice disorders. Studies were excluded if participants had been diagnosed with neurological-motor-speech disorders or who were vocally healthy. Furthermore, no medical, pharmacological, or technical instrumental treatments were used. Data Extraction and Synthesis Preferred Reporting Items for systematic reviews and meta-analyses extension statement guidelines were followed. Two reviewers independently screened citations, extracted data, and assessed risk of bias using PEDro scale. Random effects model was used for meta-analysis. Results We identified finally 12 RCT studies (treatment groups n = 285, and control group without an intervention n = 62). Eight interventions were evaluated. The only effective intervention with a significant effect was vocal function exercises (VFE) (mean pre-post difference 6.16 s, 95% confidence interval, 1.18-11.13 s). Conclusions and Relevance VFE effectively improved MPT from pre- to post-treatment in comparison with other voice interventions which were identified in the present NMA. Further high-quality intervention studies with large samples sizes, multidimensional measures, and homogeneous groups of dysphonia are needed to support evidence-based practice in laryngology.
Erstmals veröffentlicht: 19. Dezember 2022
Gesehen am 02.07.2024